"En frente de la batalla": centering the voices of Latine frontline workers in defining, understanding, and addressing community needs and solutions in tourist regions in Colorado during the COVID-19 pandemic - Lucci-Rimer, Elizabeth, author; Conner, Bradley T., advisor; Muñoz, Susana M., committee member; Riggs, Nathaniel R., committee member; Henry, Kimberly L., committee member (Colorado State University. Libraries, 2022)
Latine workers make up a significant proportion of the U.S. frontline workforce, with disproportionate representation in lower-earning positions that offer less job security. Throughout the pandemic, Latine frontline workers have faced disparate rates of COVID-19 illness, severe health impacts, death of loved ones, and economic losses. These circumstances have increased mental health difficulties, including chronic stress, depression, and anxiety. During the pandemic, Latine frontline workers in tourist communities in Colorado have suffered severe economic losses and ongoing health risks associated with frequent COVID-19 exposure and inequitable healthcare access. The present qualitative study used liberation psychology and Latino critical race theory to center the stories of Latine frontline workers in a tourist community in Colorado. Interviews were conducted with eight Latine frontline workers or spouses of frontline workers and five agency workers from nonprofits or the public sector in a tourist community in Colorado. Latine frontline community members were asked to share their stories of how their communities had experienced the pandemic, their definitions of the community's needs, and their ideas for solutions. Agency workers were asked to provide their perspectives and context. Analysis was conducted using critical qualitative inquiry and an interpretive analysis based on the theoretical frameworks. The resulting themes included community member's experiences and definitions of strengths, problems, and solutions. The results were shared in the community and recommendations were given to local agencies. This study advocates for employers, landlords, nonprofit and local government agencies, schools, and healthcare organizations to engage in equity-based structural and operational change and to assume an advocacy role in addressing underlying causes of health, mental health, educational, housing, and economic inequities.
En frente de la batalla: centering the voices of Latine frontline workers in defining, understanding, and addressing community needs and solutions in tourist regions in Colorado during the COVID-19 pandemic
Keywords: critical qualitative research; Latinx health disparities; liberation psychology; Latino critical race theory (LatCrit); COVID-19 pandemic; Latinx mental health